PENANAMAN NILAI FILANTROPI ISLAM DI LEMBAGA PENDIDIKAN (STUDI KASUS SDI SURYA BUANA KOTA MALANG) - Suherman Suherman (AL-ASASIYYA: Journal Of Basic Education, 2019)
This study seeks to present how the process of planting the value of Islamic Philanthropy in educational institutions. This study aims to investigate the planting of philanthropic values among students at the Islamic Surya Buana Elementary School in Malang. To find out the implementation of the activities of planting the value of Islamic philanthropy (zakat, infaq, and sadaqah) at SD Islam Surya Buana, Malang. This research is qualitative research with qualitative descriptive research. the results of this study indicate that the process of planting philanthropic values in educational institutions through various forms of activities such as the Friday morning charity, Palestinian fundraising and fundraising for victims of natural disasters.